Clinical Outcome of Pulsed-Radiofrequency Combined With Transforaminal Epidural Steroid Injection for Lumbosacral Radicular Pain Caused by Distinct Etiology - Liuqing Yang; Yuzhao Huang; Jiahui Ma; Zhenxing Li; Rui Han; Gangwen Guo; Yuncheng Ni; Rong Hu; Xuebin Yan; Haocheng Zhou; Haocheng Zhou; Dong Huang; et al. (Frontiers in Neuroscience, 2021)
BackgroundLumbosacral radicular pain (LSRP) can be caused by disc herniation, spinal stenosis, and failed back surgery syndrome. The clinical effect of pulsed-radiofrequency (PRF) combined with transforaminal epidural steroid injection (TESI) for radiating pain in different population remains unclear.MethodsWe retrospectively reviewed the medical recordings of patients with LSRP caused by different etiologies, who underwent PRF and TESI treatment. The primary clinical outcome was assessed by a 10-point Visual Analog Scale (VAS) pre- and post-treatment.ResultsA total of 34 LSRP patients were identified and classified into 3 subgroups (disc herniation, spinal stenosis, and failed back surgery syndrome). The overall immediate pain reduction was 4.4 ± 1.1 after procedure. After a median follow-up of 9.5 months, the VAS decreased from 6.5 ± 1.0 to 2.4 ± 1.9 at the last follow-up.ConclusionPRF combined with TESI is an effective approach to treat persistent LSRP in distinct population.